The Serbian novel after the end of utopia - Gvozden, Vladimir (Primerjalna književnost, 2020)
Numerous Serbian novels of the 1980s and 1990s turned to the treatment of an older, allegedly forgotten history which encompasses the premodern period from the Middle Ages to the Enlightenment. It seems that this shift was accompanied by a political idealism and national-emancipatory zeal after the breakup of socialist Yugoslavia and its cultural politics. This paper will critically examine three extremely successful examples of historical postmodernism in contemporary Serbian literature: Milorad Pavić's Dictionary of the Khazars (1984), Radoslav Petković's Destiny, Annotated (1993) and Goran Petrović's Opsada crkve Svetog Spasa (The Siege of the Church of Holy Salvation, 1997). This "historical turn" of historical postmodernism could be interpreted both as a deceptive attempt to return to the roots and as distinct archaeology with which writing seeks to examine the contemporary unsafe ground of the political, cultural and economic transition from the socialist system to democracy and capitalism. Actually, it seems that this kind of "reconstructive" novelistic approach, which can be seen as a deliberate postmodern double-coding, could be understood as a search for Serbian cultural capital that can be easily - perhaps too easily - found in the distant past. On the other side, the paper analyses "deconstructive" novels, like David Albahari's Bait (1996), Vladimir Tasić's Kiša i hartija (Rain and Paper, 2004) and Slobodan Tišma's Bernardijeva soba (Bernardi's Room, 2011). The novels from this camp demonstrate that the complexity connected with the demise of meta-narratives is not easy to represent in a work of literature. Through the figure of a weak subject, the "deconstructive" novel is able to imprint itself into the unknown, to disrupt codes, to cross the border and the wall of the symbolic order of capitalism and socialism and their production of desire. At the end of the paper, we try to demonstrate what paradoxes are inherent in both these types of writing.
Keywords: Albahari, David; dekonstrukcija; književnost in politika; kulturna identiteta; nacionalizem; Pavić, Milorad; Petković, Radoslav; Petrović, Goran; postmodernizem; srbska književnost; Tasić, Vladimir; Tišma, Slobodan; zgodovinski roman